2006
DOI: 10.1007/bf03174972
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activities of various essential oils against foodborne pathogenic or spoilage moulds

Abstract: The use of essential oils in the food industry, as natural sanitizing agents, requires the definition of optimal conditions. The aim of the present work was to evaluate some antimicrobial activity parameters as mycelial growth inhibition, minimum inhibitory concentration (MIC) and minimum fungicidal concentration (MFC) of six essential oils against Aspergillus niger, Aspergillus terreus, Chaetomium globosum, Penicillium chrysogenum, Penicillium pinophilum, Trichoderma harzianum and Trichoderma viride. The anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
33
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 25 publications
2
33
0
Order By: Relevance
“…However, the development of new pesticides is of interest to struggle with the evolution of resistant pathogens and to replace the compounds lost due to the new registration requirements (Dayan et al 2009). Plant extracts and essential oils have been investigated for their antimicrobial activity (Bakkali et al 2008;Isman 2000), starting from the idea that the secondary metabolism of plants have evolved to oppose pathogens (Brenner 1993 (Angelini et al 2006;Bishop and Reagan 1998;Bowers and Locke 2000;Inouye et al 2000). In a previous study we have examined the effects of TTO and of its major purified components (terpinen-4-ol, γ-terpinen and 1,8-cineole) on two mycotoxigenic fungi, i.e.…”
mentioning
confidence: 99%
“…However, the development of new pesticides is of interest to struggle with the evolution of resistant pathogens and to replace the compounds lost due to the new registration requirements (Dayan et al 2009). Plant extracts and essential oils have been investigated for their antimicrobial activity (Bakkali et al 2008;Isman 2000), starting from the idea that the secondary metabolism of plants have evolved to oppose pathogens (Brenner 1993 (Angelini et al 2006;Bishop and Reagan 1998;Bowers and Locke 2000;Inouye et al 2000). In a previous study we have examined the effects of TTO and of its major purified components (terpinen-4-ol, γ-terpinen and 1,8-cineole) on two mycotoxigenic fungi, i.e.…”
mentioning
confidence: 99%
“…As reported by several authors (Angelini et al, 2006;Wuryatmo et al, 2003), the degree of the growth of microorganisms could be related to the concentration of the active agents tested.…”
Section: Pp100_12%chlsupporting
confidence: 53%
“…Their efficiency against a large variety of pathogens and food-borne germs has been proven by recent investigations [11,13,14]. Several of the studies [1,15,16] indicated the sensitivity of Gram-positive bacteria, while others [17][18][19] have shown expressed sensitivity of Gram-negative bacteria.…”
Section: Discussionmentioning
confidence: 99%